Tinjauan Perlindungan Konsumen Air Minum Isi Ulang Bagi Masyarakat Kelurahan Gedung Johor Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Rani Sabeta Nainggolan; Majda El Muhtaj (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This study aims to determine and analyze the form of legal protection for consumers of refill drinking water in Medan City, especially in Gedung Johor Village as the research location. Consumer protection must be reviewed from the Law that has been given by the authorities as a form of protection for Indonesian citizens as a whole, both for business actors and consumers. This research is a Normative-empirical Legal research, namely research that examines the implementation of legal provisions (legislation) and written documents factually. This research was conducted using the Observation, interview, and document study methods that directly go into the field (society) with informants, namely the Medan Consumer Protection Agency, Refill Drinking Water Business Actors and Refill Drinking Water Consumers who are interrelated. The results of the study show that consumer protection for Refill Drinking Water in Gedung Johor Village as a form of government protection in accordance with the Consumer Protection Law is seen from the fulfillment of the rules set by the government as terms and conditions for selling refill drinking water in Gedung Johor Village and the obstacles in terms of this protection are the lack of public understanding of the quality of refill drinking water and the importance of consumer protection and rules that are not known by the public or consumers. This is why the government should continue to try to provide understanding through socialization, counseling, assistance and education to increase the knowledge and awareness of the Gedung Johor Village community